Activated Carbon: Advances in Research and Application - Ho Soonmin (Activated Carbon: Advances in Research and Application, 2022)
This book is mainly dealt with activated carbon which is considered as versatile adsorbent because of excellent adsorption behaviors. The adsorption studies were carried out through different models such as Langmuir model and Freundlich isotherm. Activated carbon has been used to absorb the pollutant in wastewater treatment due to adsorbent has high surface area and well-developed porosity structure. Activated carbon could also be used to remove ammonia, carbon dioxide, hydrogen sulfide, butane, propane, methane, ethylene, nitrogen oxide. Activated carbon served as dietary supplement, and suitable for adult and children.